Plantvibe / Batrisyia Zulkefly - Zulkefly, Batrisyia (2022)
Although Malaysia's construction industry has grown tremendously over the years, this industry fails to attract many local labour to involve on the ground. This research looks for factors that led to poor involvement in Malaysian contribution industry. Questionnaires were distributed to 120 employees of G5-G7 contractors in Johor. With 60% return, the data were analyzed using SPSS version 25 and resulted that low minimum wage local labour being selective in work and work status were the main factors to poor involvement of local labour in Malaysian construction industry.